Antiglare laminate
The laminate structure with a polycarbonate resin, high hardness resin, and hard coat layer addresses the lack of anti-glare and scratch resistance in liquid crystal display devices, providing effective image reflection prevention and text blur suppression with enhanced durability.
Patent Information
- Application Number
- JP2021540683
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-08-20
- Filing Date
- 2020-07-22
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2040-07-22
AI Technical Summary
Existing front panels for liquid crystal display devices lack a combination of anti-glare performance, high scratch resistance, and shape stability, with the addition of fine particles compromising scratch resistance and causing image blurring.
A laminate structure comprising a polycarbonate resin layer, a high hardness resin layer, and a hard coat layer with an uneven shape, where the high hardness resin layer is between the polycarbonate resin layer and the hard coat layer, and the hard coat layer has a thickness of 10 to 250 μm, with a total laminate thickness of 100 to 3,000 μm, and a specific resin composition that includes copolymers and acrylic hard coat layers.
The laminate achieves anti-glare performance, high scratch resistance, and excellent shape stability, preventing image reflection and blurring while maintaining structural integrity.
Smart Images

Figure 0007607567000024 
Figure 0007607567000025 
Figure 0007607567000026
Abstract
Description
[Technical field]
[0001] The present invention relates to an antiglare laminate. More specifically, the present invention relates to an antiglare laminate that has antiglare performance, high scratch resistance, and excellent shape stability, and is used as a front panel of an in-vehicle liquid crystal display device, a mobile phone terminal, a personal computer, or a tablet PC.
[0002] Liquid crystal display devices are provided with a front panel for the purpose of protecting the liquid crystal panel, etc. Materials used for the front panel of conventional liquid crystal display devices include (meth)acrylic resins, such as polymethyl methacrylate (PMMA).
[0003] In recent years, sheets made of polycarbonate resin have been used as front panels because of their high impact resistance, heat resistance, secondary processability, light weight, transparency, etc. In particular, front panels in which a hard coat is applied to a multilayer sheet in which an acrylic resin is laminated on the surface of a polycarbonate resin sheet have surface hardness and scratch resistance comparable to conventional acrylic resins with hard coats, while also possessing the excellent impact resistance, heat resistance, processability, and transparency of polycarbonate resin, and are therefore widely used as front panels.
[0004] The front panel of a liquid crystal display device having the above-mentioned polycarbonate resin sheet is generally formed by melt extrusion together with an acrylic resin.
[0005] In liquid crystal display devices, an anti-reflection optical laminate is generally provided on the outermost surface. Such an anti-reflection optical laminate suppresses image glare and reduces reflectance by scattering or interfering with light.
[0006] As one of the anti-reflection optical laminates, an anti-glare film is known in which an anti-glare layer having an uneven surface is formed on the surface of a transparent substrate. This anti-glare film can prevent the deterioration of visibility due to the reflection of the outside light or the reflection of an image by scattering the outside light by the uneven surface. In addition, since this optical laminate is usually placed on the outermost surface of a liquid crystal display device, it is also required to impart hard coat properties to prevent scratches during handling.
[0007] In the display surfaces of liquid crystal display devices and organic electroluminescence (EL) display devices, a mixture of fine particles and a binder resin or a curable resin is usually applied to a substrate, and fine irregularities are formed on the surface to prevent regular reflection and prevent image glare. However, when an irregular shape is provided to prevent image glare, the scattering of transmitted light that travels straight increases, making the outlines of pixels unclear and causing blurred characters.
[0008] Furthermore, if fine particles are added to create surface irregularities, the fine particles on the outermost surface fall off during the scratch resistance test and act as an abrasive, resulting in a significant decrease in scratch resistance compared to when fine particles are not added, which is not preferred.
[0009] As described above, there have been no front panels for in-vehicle liquid crystal display devices, mobile phone terminals, personal computers, and tablet PCs that have excellent impact resistance, heat resistance, and anti-glare properties that prevent image reflections and suppress character blurring, as well as high scratch resistance and excellent shape stability. In Patent Document 1, fine particles are added to improve the transmission clarity and reduce blurred characters. Adding fine particles improves the pencil hardness, but it is not preferable because it reduces the scratch resistance. [Prior art documents] [Patent documents]
[0010] Patent Document 1: JP 2010-160398 A DISCLOSURE OF THEINVENTION [Problem to be solved by the invention]
[0011] The present invention aims to solve at least one of the above-mentioned problems in the prior art. Another object of the present invention is to provide an antiglare laminate having antiglare performance that combines the performance of preventing image reflection and the suppression of character blurring, high scratch resistance, and excellent shape stability. [Means for solving the problem]
[0012] The above problems can be solved by the present invention. That is, the present invention is as follows. <1> A layer containing a resin (A) containing a polycarbonate resin (a1); a layer containing a high-hardness resin (B) provided on at least one surface of a layer containing a resin (A) including a polycarbonate resin (a1); a hard coat layer having an uneven shape and provided on the layer containing a high-hardness resin (B); and an antiglare laminate satisfying the following conditions (i) and (ii): (i) the thickness of the layer containing the high-hardness resin (B) is 10 to 250 μm, and the total thickness of the layer containing the resin (A) including the polycarbonate resin (a1) and the layer containing the high-hardness resin (B) is 100 to 3,000 μm; (ii) The laminate is an antiglare laminate in which T1 / T2 is 2.0 or more, where T1 is the transmitted clarity when light is transmitted through an optical comb having a width of 2.0 mm, and T2 is the reflected clarity measured at an incident angle of 45° using an optical comb having a width of 2.0 mm.
[0013] <2> The transmission clarity T1 when light is transmitted through a 2.0 mm wide optical comb satisfies 30%≦T1≦50%, and the reflection clarity T2 measured at an incident angle of 45° using a 2.0 mm wide optical comb satisfies 10%≦T2≦20%. <1> The antiglare laminate according to claim 1. <3> The high hardness resin (B) contains at least one selected from the group consisting of the following resins (B1) to (B5): The resin (B1) is A copolymer resin comprising (a) a (meth)acrylic acid ester structural unit represented by the following general formula (1) and (b) an aliphatic vinyl structural unit represented by the following general formula (2), wherein the total proportion of the (meth)acrylic acid ester structural unit (a) and the aliphatic vinyl structural unit (b) is 90 to 100 mol % of all structural units of the copolymer resin, and the proportion of the (meth)acrylic acid ester structural unit (a) is 65 to 80 mol % of all structural units of the copolymer resin: [ka] (In the formula, R1 is a hydrogen atom or a methyl group, and R2 is an alkyl group having 1 to 18 carbon atoms.) [ka] (In the formula, R3 is a hydrogen atom or a methyl group, and R4 is a cyclohexyl group which may have a hydrocarbon group having 1 to 4 carbon atoms.) and The resin (B2) is the resin (B1) is 35 to 65% by mass, and the styrene-unsaturated dicarboxylic acid copolymer (C) is 35 to 65% by mass, the styrene-unsaturated dicarboxylic acid copolymer (C) is a resin containing 65 to 90% by mass of a styrene monomer unit (c1) and 10 to 35% by mass of an unsaturated dicarboxylic anhydride monomer unit (c2); The resin (B3) is The present invention relates to a resin composition comprising: 55 to 10 mass% of a resin (D) containing a vinyl monomer; and 45 to 90 mass% of a styrene-unsaturated dicarboxylic acid copolymer (E); the styrene-unsaturated dicarboxylic acid copolymer (E) is a resin comprising 50 to 80 mass% of a styrene monomer unit (e1), 10 to 30 mass% of an unsaturated dicarboxylic acid monomer unit (e2), and 5 to 30 mass% of a vinyl monomer unit (e3); The resin (B4) is a resin copolymer (G) containing 5 to 20 mass% of styrene structural units, 60 to 90 mass% of (meth)acrylic acid ester structural units, and 5 to 20 mass% of an N-substituted maleimide monomer, or an alloy of the resin copolymer (G) and the copolymer (E); The resin (B5) is A copolymer containing a structural unit (H) represented by the following formula (3) and, optionally, a structural unit (J) represented by the following formula (4): [ka] [ka] <1> or <2> The antiglare laminate according to claim 1.
[0014] <4> The hard coat layer having a concave-convex shape does not contain inorganic particles or organic particles. <1> ~ <3> 13. The antiglare laminate according to claim 12, <5> The hard coat layer having a concave-convex shape has at least one of anti-reflection performance, antifouling performance, antistatic performance, and weather resistance. <1> ~ <4> 13. The antiglare laminate according to claim 12, <6> A second hard coat layer is provided on the surface opposite to the hard coat layer having the unevenness. <1> ~ <5> 13. The antiglare laminate according to claim 12, <7> The second hard coat layer has at least one of anti-reflection performance, antifouling performance, antistatic performance, and weather resistance. <6> The antiglare laminate according to claim 1. <8> The polycarbonate resin (a1) contains a component derived from a monohydric phenol represented by the following general formula (5): <1> ~ <7> 13. The antiglare laminate according to claim 12, [ka] (In the formula, R1 represents an alkyl group having 8 to 36 carbon atoms or an alkenyl group having 8 to 36 carbon atoms, and R2 to R5 each independently represent a hydrogen atom, a halogen, or an alkyl group having 1 to 20 carbon atoms or an aryl group having 6 to 12 carbon atoms which may have a substituent, and the substituent is a halogen, an alkyl group having 1 to 20 carbon atoms, or an aryl group having 6 to 12 carbon atoms.) <9> the above <1> ~ <8> 2. An in-vehicle display device comprising the antiglare laminate according to claim 1. <10> the above <1> ~ <8> 2. A touch panel front protection plate comprising the antiglare laminate according to any one of claims 1 to 11. <11> the above <1> ~ <8> 2. A front panel for office automation equipment, portable electronic equipment, or television, comprising the antiglare laminate according to any one of claims 1 to 11. <12> the above <1> ~ <8> 2. A method for producing an antiglare laminate according to claim 1, comprising the step of transferring a concave-convex shape to the hard coat layer by pressing a patterned PET film onto the photocurable resin composition on the layer containing the high-hardness resin (B). Effect of the Invention
[0015] According to the present invention, it is possible to provide an antiglare laminate which has antiglare performance, high scratch resistance, and excellent shape stability and is used as a front panel of an in-vehicle liquid crystal display device, a mobile phone terminal, a personal computer, or a tablet PC. [Brief description of the drawings]
[0016] [Figure 1] 1 is a photograph taken with a white microscope showing the uneven shape of the laminate obtained in Example 1 that prevents reflections and suppresses blurring of characters. [Diagram 2] 1 is a photograph taken with a white microscope showing the uneven shape of the laminate obtained in Comparative Example 1, which is excellent only in preventing reflection. [Diagram 3] 1 is a photograph taken by a white microscope showing the uneven shape of the laminate obtained in Comparative Example 2, which is excellent only in suppressing blurring of characters. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] Hereinafter, the present invention will be described in detail by way of examples and working examples. However, the present invention is not limited to the illustrated examples and working examples, and can be modified in any manner without departing from the scope of the present invention.
[0018] The antiglare laminate of the present invention (hereinafter sometimes referred to as "resin sheet") has a layer (hereinafter sometimes referred to as "substrate layer") containing a resin (A) containing a polycarbonate resin (a1), and a layer (hereinafter sometimes referred to as "high-hardness resin layer" or "high-hardness layer") containing a high-hardness resin (B) and a hard coat layer having an uneven shape provided on at least one surface of the layer (hereinafter sometimes referred to as "substrate layer") containing a resin (A) containing a polycarbonate resin (a1). The substrate layer may be a layer made of a resin (A) containing a polycarbonate resin (a1). The high-hardness layer may be a layer made of a high-hardness resin (B).
[0019] In terms of the order of lamination, the high-hardness resin layer is present between the substrate layer and the hard-coat layer, and the hard-coat layer, which is the outermost layer, is provided with an uneven surface. The other side of the layer containing the resin (A) containing the polycarbonate resin (a1) is not particularly specified, but both the high-hardness resin layer and the hard-coat layer, or either one of them, may be provided.
[0020] For the high-hardness resin layer, it is desirable to use a resin selected from the high-hardness resins (B). Furthermore, when high-hardness resin layers are provided on both sides of the base layer, it is more desirable to use the same high-hardness resin (B) on both sides in terms of shape stability.
[0021] In one embodiment of the present invention, the hard coat layer has an uneven shape. When hard coat layers are formed on both sides, it is more preferable to provide similar hard coat layers because this improves shape stability.
[0022] In one embodiment of the present invention, the antiglare laminate can be used, for example, as a full-surface protective plate for touch panels of in-vehicle display devices such as car navigation systems, center information displays (CIDs), rear seat entertainment (RSEs), and clusters, as well as a front panel for office automation equipment, portable electronic devices, or televisions. In addition, for example, the front panel can be used alone as the front panel of a liquid crystal display device, but it may also be used as a front panel in a composite manner, for example by laminating it with another substrate such as a touch sensor.
[0023] Each of the components of the antiglare laminate of the present invention will be described below.
[0024] (Resin (A) containing polycarbonate resin (a1)) The resin (A) containing the polycarbonate resin (a1) used in the present invention is a resin containing mainly the polycarbonate resin (a1). The content of the polycarbonate resin (a1) in the resin (A) is 75% by mass or more, but since impact resistance is improved by increasing the content, it is preferably 90% by mass or more, and more preferably 100% by mass.
[0025] The polycarbonate resin (al) is not particularly limited as long as it contains a carbonate bond, i.e., -[OR-OCO]- unit (wherein R is an aliphatic group, an aromatic group, or both an aliphatic group and an aromatic group, and further has a straight-chain structure or a branched structure), in the molecular main chain, but it is particularly preferable to use a polycarbonate resin containing a structural unit of the following formula (4). By using such a polycarbonate resin, an antiglare laminate having excellent impact resistance can be obtained.
[0026] [ka]
[0027] Specifically, the polycarbonate resin (a1) may be an aromatic polycarbonate resin (for example, manufactured by Mitsubishi Engineering Plastics Corporation, product names: Iupilon S-2000, Iupilon S-1000, Iupilon E-2000), but is not limited thereto.
[0028] Furthermore, in recent years, there has been an increasing demand for bending the front panel as well, and therefore, as the polycarbonate resin (al), a resin using a monohydric phenol represented by the following general formula (5) as an end terminator is preferred.
[0029] [ka]
[0030] (In the formula, R1 represents an alkyl group having 8 to 36 carbon atoms or an alkenyl group having 8 to 36 carbon atoms, and R2 to R5 each independently represent a hydrogen atom, a halogen, or an alkyl group having 1 to 20 carbon atoms or an aryl group having 6 to 12 carbon atoms which may have a substituent, and the substituent is a halogen, an alkyl group having 1 to 20 carbon atoms, or an aryl group having 6 to 12 carbon atoms.)
[0031] More preferably, the monohydric phenol represented by general formula (5) is represented by the following general formula (6).
[0032] [ka] (In the formula, R1 represents an alkyl group having 8 to 36 carbon atoms or an alkenyl group having 8 to 36 carbon atoms.)
[0033] The number of carbon atoms in R1 in general formula (5) or general formula (6) is more preferably within a specific numerical range. Specifically, the upper limit of the number of carbon atoms in R1 is preferably 36, more preferably 22, and particularly preferably 18. The lower limit of the number of carbon atoms in R1 is preferably 8, and more preferably 12. 。
[0034] Among the monohydric phenols (end terminators) represented by general formula (5) or general formula (6), it is particularly preferable to use either or both of parahydroxybenzoic acid hexadecyl ester and parahydroxybenzoic acid 2-hexyldecyl ester as the end terminator.
[0035] In the case where R1 in the general formula (6) is, for example, a monohydric phenol (terminal terminator) which is an alkyl group having 16 carbon atoms, the glass transition temperature, melt fluidity, moldability, drawdown resistance, and solvent solubility of the monohydric phenol during the production of the polycarbonate resin are excellent, and it is particularly preferable as the terminal terminator used for the polycarbonate resin in the present invention.
[0036] On the other hand, if the number of carbon atoms in R1 in general formula (5) or general formula (6) is too large, the solubility of the monohydric phenol (end terminator) in organic solvents tends to decrease, which may result in a decrease in productivity during the production of the polycarbonate resin.
[0037] For example, when the carbon number of R1 is 36 or less, the productivity is high and the economic efficiency is good in producing a polycarbonate resin. When the carbon number of R1 is 22 or less, the monohydric phenol has particularly excellent solubility in organic solvents, and the productivity in producing a polycarbonate resin can be extremely high and the economic efficiency is improved.
[0038] If the number of carbon atoms in R1 in general formula (5) or general formula (6) is too small, the glass transition temperature of the polycarbonate resin will not be a sufficiently low value, and the thermoformability may decrease.
[0039] In the present invention, the weight average molecular weight of the polycarbonate resin (al) affects the impact resistance and molding conditions of the antiglare laminate. That is, if the weight average molecular weight is too small, the impact resistance of the antiglare laminate decreases, which is not preferable. If the weight average molecular weight is too high, an excessive heat source may be required when laminating a layer containing the polycarbonate resin (al), which is not preferable. In addition, since a high temperature is required depending on the molding method, the polycarbonate resin (al) is exposed to a high temperature, which may adversely affect its thermal stability. The weight average molecular weight of the polycarbonate resin (al) is preferably 15,000 to 75,000, more preferably 20,000 to 70,000. It is further preferably 25,000 to 65,000. The weight average molecular weight is a weight average molecular weight measured by gel permeation chromatography (GPC) in terms of standard polystyrene.
[0040] The resin (A) may further contain additives. As the additives, those usually used in resin sheets can be used. As the additives, for example, antioxidants, anti-coloring agents, anti-static agents, release agents, lubricants, dyes, pigments, plasticizers, flame retardants, resin modifiers, compatibilizers, reinforcing materials such as organic fillers and inorganic fillers can be mentioned. The method of mixing the additives and the resin is not particularly limited, and a method of compounding the entire amount, a method of dry blending a master batch, a method of dry blending the entire amount, etc. can be used. The amount of the additive is preferably 0 to 10 mass % relative to the total mass of the base layer, more preferably 0 to 7 mass %, and particularly preferably 0 to 5 mass %.
[0041] (High hardness resin (B)) The high hardness resin (B) used in the present invention includes at least one selected from the group consisting of high hardness resin (B1), high hardness resin (B2), high hardness resin (B3), high hardness resin (B4), and high hardness resin (B5).
[0042] <High hardness resin (B1)> The high-hardness resin (B1) used in the present invention is a copolymer resin containing (meth)acrylic acid ester structural units (a) represented by general formula (1) and aliphatic vinyl structural units (b) represented by general formula (2), in which the total proportion of the methacrylic acid ester structural units (a) and the aliphatic vinyl structural units (b) is 90 to 100 mol % of all structural units of the copolymer resin, and the proportion of the methacrylic acid ester structural units (a) is 65 to 80 mol % of all structural units of the copolymer resin.
[0043] [ka] (In the formula, R1 is a hydrogen atom or a methyl group, and R2 is an alkyl group having 1 to 18 carbon atoms.)
[0044] [ka] (In the formula, R3 is a hydrogen atom or a methyl group, and R4 is a cyclohexyl group which may have a hydrocarbon group having 1 to 4 carbon atoms.)
[0045] In this specification, the "hydrocarbon group" may be linear, branched, or cyclic, and may have a substituent.
[0046] In the (meth)acrylic acid ester structural unit (a) represented by general formula (1), R2 is an alkyl group having 1 to 18 carbon atoms, preferably an alkyl group having 1 to 10 carbon atoms, and more preferably an alkyl group having 1 to 6 carbon atoms. Specific examples include a methyl group, an ethyl group, a butyl group, a lauryl group, a stearyl group, a cyclohexyl group, and an isobornyl group.
[0047] Of the (meth)acrylic acid ester structural units (a), preferred are (meth)acrylic acid ester structural units in which R2 is a methyl group or an ethyl group, and more preferred are methyl methacrylate structural units in which R1 is a methyl group and R2 is a methyl group.
[0048] In the aliphatic vinyl structural unit (b) represented by the general formula (2), R3 is a hydrogen atom or a methyl group, and more preferably a hydrogen atom. R4 is a cyclohexyl group or a cyclohexyl group having a hydrocarbon group having 1 to 4 carbon atoms. Among the aliphatic vinyl structural units (b), more preferred are those in which R3 is a hydrogen atom and R4 is a cyclohexyl group.
[0049] The high-hardness resin (B1) may contain one or more types of the (meth)acrylic acid ester structural unit (a), and may contain one or more types of the aliphatic vinyl structural unit (b).
[0050] The total proportion of the (meth)acrylic acid ester structural unit (a) and the aliphatic vinyl structural unit (b) is 90 to 100 mol %, preferably 95 to 100 mol %, and more preferably 98 to 100 mol %, based on the total of all structural units of the copolymer resin.
[0051] That is, the high-hardness resin (B1) may contain a structural unit other than the (meth)acrylic acid ester structural unit (a) and the aliphatic vinyl structural unit (b). The amount of the structural unit is preferably 10 mol % or less, more preferably 5 mol % or less, and particularly preferably 2 mol % or less, based on the total structural units of the resin (B1).
[0052] Examples of structural units other than the (meth)acrylic acid ester structural unit (a) and the aliphatic vinyl structural unit (b) include structural units derived from aromatic vinyl monomers containing an unhydrogenated aromatic double bond, which are generated in the process of producing resin (B1) by polymerizing a (meth)acrylic acid ester monomer and an aromatic vinyl monomer and then hydrogenating the aromatic double bond derived from the aromatic vinyl monomer.
[0053] The content of the (meth)acrylic acid ester structural unit (a) represented by the general formula (1) is preferably 65 to 80 mol %, more preferably 70 to 80 mol %, based on the total structural units in the high hardness resin (B1). When the ratio of the (meth)acrylic acid ester structural unit (a) to the total structural units in the resin (B1) is 65 mol % or more, a resin layer having excellent adhesion to the substrate layer and excellent surface hardness can be obtained. When the ratio is 80 mol % or less, warping due to water absorption of the resin sheet is unlikely to occur.
[0054] The content of the aliphatic vinyl structural unit (b) represented by the general formula (2) is preferably 20 to 35 mol %, more preferably 20 to 30 mol %, based on the total structural units in the high hardness resin (B1). If the content of the aliphatic vinyl structural unit (b) is 20 mol % or more, warping under high temperature and high humidity conditions can be prevented, and if it is 35 mol % or less, peeling at the interface with the base layer can be prevented.
[0055] In this specification, the "copolymer" may have any of a random, block, and alternating copolymer structure.
[0056] The method for producing the high hardness resin (B1) is not particularly limited, but it is preferable to use a resin obtained by polymerizing at least one (meth)acrylic acid ester monomer and at least one aromatic vinyl monomer, and then hydrogenating the aromatic double bond derived from the aromatic vinyl monomer. Note that (meth)acrylic acid refers to methacrylic acid and / or acrylic acid. Specific examples of the aromatic vinyl monomer used in this case include styrene, α-methylstyrene, p-hydroxystyrene, alkoxystyrene, chlorostyrene, and derivatives thereof. Among these, styrene is preferred.
[0057] For the polymerization of the (meth)acrylic acid ester monomer and the aromatic vinyl monomer, a known method can be used, for example, the copolymer can be produced by a bulk polymerization method, a solution polymerization method, etc. The bulk polymerization method is carried out by continuously supplying a monomer composition containing the above-mentioned monomer and a polymerization initiator to a complete mixing tank and continuously polymerizing the monomer at 100 to 180°C. The above-mentioned monomer composition may contain a chain transfer agent as necessary.
[0058] The polymerization initiator is not particularly limited, but includes organic peroxides such as t-amylperoxy-2-ethylhexanoate, t-butylperoxy-2-ethylhexanoate, benzoyl peroxide, 1,1-di(t-hexylperoxy)-3,3,5-trimethylcyclohexane, 1,1-di(t-hexylperoxy)cyclohexane, 1,1-di(t-butylperoxy)cyclohexane, t-hexylpropoxyisopropyl monocarbonate, t-amylperoxy normal octoate, t-butylperoxyisopropyl monocarbonate, and di-t-butyl peroxide, and azo compounds such as 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile), and 2,2'-azobis(2,4-dimethylvaleronitrile). These can be used alone or in combination of two or more.
[0059] A chain transfer agent is used as necessary, and an example of such an agent is α-methylstyrene dimer.
[0060] Examples of solvents used in the solution polymerization method include hydrocarbon solvents such as toluene, xylene, cyclohexane, and methylcyclohexane; ester solvents such as ethyl acetate and methyl isobutyrate; ketone solvents such as acetone and methyl ethyl ketone; ether solvents such as tetrahydrofuran and dioxane; and alcohol solvents such as methanol and isopropanol.
[0061] The solvent used in the hydrogenation reaction after polymerization of the (meth)acrylic acid ester monomer and the aromatic vinyl monomer may be the same as or different from the solvent used in the solution polymerization method described above. Examples of the solvent include hydrocarbon solvents such as cyclohexane and methylcyclohexane, ester solvents such as ethyl acetate and methyl isobutyrate, ketone solvents such as acetone and methyl ethyl ketone, ether solvents such as tetrahydrofuran and dioxane, and alcohol solvents such as methanol and isopropanol.
[0062] After the (meth)acrylic acid ester monomer and the aromatic vinyl monomer are polymerized as described above, the aromatic double bond derived from the aromatic vinyl monomer is hydrogenated to obtain the high hardness resin (B1) used in the present invention.
[0063] The hydrogenation method is not particularly limited, and known methods can be used. For example, the hydrogenation can be carried out in a batch or continuous flow manner at a hydrogen pressure of 3 to 30 MPa and a reaction temperature of 60 to 250°C. By keeping the temperature at 60°C or higher, the reaction time does not take too long, and by keeping the temperature at 250°C or lower, cleavage of molecular chains and hydrogenation of ester moieties are unlikely to occur.
[0064] Examples of catalysts used in the hydrogenation reaction include solid catalysts in which metals such as nickel, palladium, platinum, cobalt, ruthenium, and rhodium, or oxides, salts, or complex compounds of these metals are supported on porous supports such as carbon, alumina, silica, silica-alumina, and diatomaceous earth.
[0065] The high-hardness resin (B1) is preferably one in which 70% or more of the aromatic double bonds derived from aromatic vinyl monomers are hydrogenated. That is, the ratio of unhydrogenated sites of aromatic double bonds in the structural units derived from aromatic vinyl monomers is preferably 30% or less. If it exceeds 30%, the transparency of the high-hardness resin (B1) may decrease. The ratio of unhydrogenated sites is more preferably less than 10%, and even more preferably less than 5%.
[0066] The weight average molecular weight of the high hardness resin (B1) is not particularly limited, but from the viewpoint of strength and moldability, it is preferably 50,000 to 400,000, and more preferably 70,000 to 300,000. The weight average molecular weight is a weight average molecular weight measured by gel permeation chromatography (GPC) and converted into standard polystyrene.
[0067] The high-hardness resin (B1) can be blended with other resins as long as the transparency is not impaired, such as methyl methacrylate-styrene copolymer resin, polymethyl methacrylate, polystyrene, polycarbonate, cycloolefin (co)polymer resin, acrylonitrile-styrene copolymer resin, acrylonitrile-butadiene-styrene copolymer resin, and various elastomers.
[0068] The glass transition temperature of the high-hardness resin (B1) is preferably in the range of 110 to 140° C. When the glass transition temperature is 110° C. or higher, the laminate provided by the present invention is less likely to deform or crack in a heat environment or a humid heat environment, and when the glass transition temperature is 140° C. or lower, the laminate is excellent in processability, such as continuous thermal shaping using a mirror roll or a shaping roll, or batch-type thermal shaping using a mirror mold or a shaping mold. The glass transition temperature in the present invention is the temperature measured using a differential scanning calorimeter with a 10 mg sample at a heating rate of 10° C. / min and calculated by the midpoint method.
[0069] Examples of the high hardness resin (B1) include, but are not limited to, Optimus 7500 and 6000 (manufactured by Mitsubishi Gas Chemical Company).
[0070] <High hardness resin (B2)> The high-hardness resin (B2) used in the present invention is a resin containing 35 to 65 mass% of a high-hardness resin (B1) and 35 to 65 mass% of a styrene-unsaturated dicarboxylic acid copolymer (C), and the styrene-unsaturated dicarboxylic acid copolymer (C) contains 65 to 90 mass% of a styrene monomer unit (c1) and 10 to 35 mass% of an unsaturated dicarboxylic anhydride monomer unit (c2).
[0071] The styrene-unsaturated dicarboxylic acid copolymer (C) will be described below.
[0072] <Styrene-unsaturated dicarboxylic acid copolymer (C)> The styrene-unsaturated dicarboxylic acid copolymer (C) used in the present invention contains a styrene monomer unit (c1) and an unsaturated dicarboxylic acid anhydride monomer unit (c2).
[0073] <Styrene-based monomer unit (c1)> The styrene monomer is not particularly limited, and any known styrene monomer can be used, but from the viewpoint of availability, styrene, a-methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, t-butylstyrene, etc. are listed. Among these, styrene is particularly preferred from the viewpoint of compatibility. Two or more of these styrene monomers may be mixed.
[0074] <Unsaturated dicarboxylic acid anhydride monomer unit (c2)> Examples of the unsaturated dicarboxylic anhydride monomer include acid anhydrides such as maleic acid, itaconic acid, citraconic acid, and aconitic acid, and maleic anhydride is preferred from the viewpoint of compatibility with vinyl monomers. Two or more of these unsaturated dicarboxylic anhydride monomers may be mixed.
[0075] <Composition ratio of styrene-unsaturated dicarboxylic acid copolymer (C)> The composition ratio of the styrene-unsaturated dicarboxylic acid copolymer (C) is 65 to 90 mass% (preferably 70 to 85 mass%) of styrene monomer units (c1) and 10 to 35 mass% (preferably 15 to 30 mass%) of unsaturated dicarboxylic anhydride monomer units (c2).
[0076] Specific examples of the copolymer (C) include XIBOND140 and XIBOND160 manufactured by POLYSCOPE POLYMERS BV, but are not limited thereto.
[0077] <High hardness resin (B3)> The high-hardness resin (B3) used in the present invention is a resin containing 55 to 10 mass % (preferably 50 to 20 mass %) of a resin (D) containing a vinyl monomer, and 45 to 90 mass % (preferably 50 to 80 mass %) of a styrene-unsaturated dicarboxylic acid copolymer (E), wherein the styrene-unsaturated dicarboxylic acid copolymer (E) contains 50 to 80 mass % of a styrene monomer unit (e1), 10 to 30 mass % of an unsaturated dicarboxylic anhydride monomer unit (e2), and 5 to 30 mass % of a vinyl monomer unit (e3).
[0078] The vinyl monomer-containing resin (D) and the styrene-unsaturated dicarboxylic acid copolymer (E) will be described below in turn.
[0079] <Resin containing vinyl monomer (D)> The vinyl monomer-containing resin (D) used in the present invention may be, for example, a homopolymer of vinyl monomers such as acrylonitrile, methacrylonitrile, acrylic acid, methyl acrylate, ethyl acrylate, n-butyl acrylate, 2-ethylhexyl acrylate, methacrylic acid, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, and 2-ethylhexyl methacrylate, and the monomer unit is particularly preferably methyl methacrylate. Also, a copolymer containing two or more of the above monomer units may be used. The weight average molecular weight of the vinyl monomer-containing resin (D) is preferably 10,000 to 500,000, and more preferably 50,000 to 300,000.
[0080] <Styrene-unsaturated dicarboxylic acid copolymer (E)> The styrene-unsaturated dicarboxylic acid copolymer (E) used in the present invention contains a styrene monomer unit (e1), an unsaturated dicarboxylic anhydride monomer unit (e2), and a vinyl monomer unit (e3).
[0081] <Styrene-based monomer unit (e1)> The styrene monomer is not particularly limited, and any known styrene monomer can be used, but from the viewpoint of availability, styrene, a-methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, t-butylstyrene, etc. are listed. Among these, styrene is particularly preferred from the viewpoint of compatibility. Two or more of these styrene monomers may be mixed.
[0082] <Unsaturated dicarboxylic anhydride monomer unit (e2)> Examples of the unsaturated dicarboxylic anhydride monomer include acid anhydrides such as maleic acid, itaconic acid, citraconic acid, and aconitic acid, and maleic anhydride is preferred from the viewpoint of compatibility with vinyl monomers. Two or more of these unsaturated dicarboxylic anhydride monomers may be mixed.
[0083] <Vinyl monomer unit (e3)> Examples of vinyl monomers include acrylonitrile, methacrylonitrile, acrylic acid, methyl acrylate, ethyl acrylate, n-butyl acrylate, 2-ethylhexyl acrylate, methacrylic acid, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, and 2-ethylhexyl methacrylate. From the viewpoint of compatibility with the resin (D) containing a vinyl monomer, methyl methacrylate (MMA) is preferred. Two or more of these vinyl monomers may be mixed.
[0084] <Composition ratio of styrene-unsaturated dicarboxylic acid copolymer (E)> The composition ratio of the styrene-unsaturated dicarboxylic acid copolymer (E) is 50 to 80 mass% (preferably 50 to 75 mass%) of styrene monomer units (e1), 10 to 30 mass% (preferably 10 to 25 mass%) of unsaturated dicarboxylic anhydride monomer units (e2), and 5 to 30 mass% (preferably 7 to 27 mass%) of vinyl monomer units (e3).
[0085] The weight average molecular weight of the styrene-unsaturated dicarboxylic acid copolymer (E) is preferably 50,000 to 200,000, more preferably 80,000 to 200,000. When the weight average molecular weight is 50,000 to 200,000, the compatibility with the resin (D) containing a vinyl monomer is good, and the effect of improving heat resistance is excellent. The weight average molecular weights of the resin (D) and the copolymer (E) are weight average molecular weights measured by gel permeation chromatography (GPC) in terms of standard polystyrene.
[0086] Specific examples of the copolymer (E) include Resisfy R100, R200, and R310 (manufactured by Denki Kagaku Kogyo Co., Ltd.), and Delpet 980N (manufactured by Asahi Kasei Chemical Co., Ltd.), but are not limited thereto.
[0087] <High hardness resin (B4)> The high-hardness resin (B4) used in the present invention is a resin copolymer (G) containing 5 to 20 mass% of styrene structural units, 60 to 90 mass% of (meth)acrylic acid ester structural units, and 5 to 20 mass% of N-substituted maleimide monomers, or an alloy of the resin copolymer (G) and the copolymer (E).
[0088] Examples of the N-substituted maleimide monomer in the resin copolymer (G) include N-aryl maleimides such as N-phenyl maleimide, N-chlorophenyl maleimide, N-methylphenyl maleimide, N-naphthyl maleimide, N-hydroxyphenyl maleimide, N-methoxyphenyl maleimide, N-carboxyphenyl maleimide, N-nitrophenyl maleimide, and N-tribromophenyl maleimide, and N-phenyl maleimide is preferred from the viewpoint of compatibility with acrylic resins. Two or more of these N-substituted maleimide monomers may be mixed. The content of the N-substituted maleimide monomer is 5 to 20% by mass, preferably 5 to 15% by mass, and more preferably 5 to 10% by mass, based on the total amount of the high hardness resin (B4).
[0089] The styrene structural unit is not particularly limited, and any known styrene-based monomer can be used, but examples thereof include styrene, methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, and t-butylstyrene, from the viewpoint of availability. Among these, styrene is particularly preferred from the viewpoint of compatibility. Two or more of these styrene-based monomers may be mixed. The content of the styrene structural unit is 5 to 20% by mass, preferably 5 to 15% by mass, and more preferably 5 to 10% by mass, based on the total mass of the high-hardness resin (B4).
[0090] Examples of (meth)acrylic acid ester constituent units include acrylic acid, methyl acrylate, ethyl acrylate, n-butyl acrylate, 2-ethylhexyl acrylate, methacrylic acid, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, etc., and methyl methacrylate is particularly preferred as a monomer unit. Also, copolymers containing two or more of the above monomer units may be used.
[0091] The content of the (meth)acrylic acid ester constituent units is from 60 to 90 mass %, preferably from 70 to 90 mass %, and more preferably from 80 to 90 mass %, based on the total mass of the high-hardness resin (B4).
[0092] The method for producing the resin copolymer (G) is not particularly limited, but it can be produced by solution polymerization, bulk polymerization, or the like.
[0093] Examples of the resin copolymer (G) include, but are not limited to, Delpet PM120N (manufactured by Asahi Kasei Chemical Corporation).
[0094] The weight average molecular weight of the resin copolymer (G) is preferably from 50,000 to 250,000, and more preferably from 100,000 to 200,000.
[0095] <High hardness resin (B5)> The high hardness resin (B5) is a copolymer containing a structural unit (H) represented by the following formula (3) and, optionally, a structural unit (J) represented by the following formula (4). The high hardness resin (B5) may or may not contain the structural unit (J), but preferably contains it. [ka] [ka]
[0096] The proportion of the structural unit (H) in all structural units of the high hardness resin (B5) is preferably 50 to 100 mol%, more preferably 60 to 100 mol%, and particularly preferably 70 to 100 mol%. The proportion of the structural unit (J) in all structural units of the high hardness resin (B5) is preferably 0 to 50 mol%, more preferably 0 to 40 mol%, and particularly preferably 0 to 30 mol%.
[0097] The total content of the structural unit (H) and the structural unit (J) is preferably 90 to 100 mol %, more preferably 95 to 100 mol %, and particularly preferably 98 to 100 mol %, based on the high hardness resin (B5).
[0098] The high hardness resin (B5) may contain a structural unit other than the structural unit (H) and the structural unit (J). When the other structural units are contained, the amount thereof is preferably 10 mol % or less, more preferably 5 mol % or less, and particularly preferably 2 mol % or less, based on the total structural units of the high hardness resin (B5).
[0099] The method for producing the high hardness resin (B5) is not particularly limited, but it can be produced by the same method as the above-mentioned method for producing the polycarbonate resin (a1) except that bisphenol C is used as the monomer.
[0100] Examples of high hardness resins (B5) include, but are not limited to, Iupilon KH3410UR, KH3520UR, and KS3410UR (manufactured by Mitsubishi Engineering Plastics Corporation).
[0101] The weight average molecular weight of the high-hardness resin (B5) is preferably from 15,000 to 75,000, more preferably from 20,000 to 70,000, and particularly preferably from 25,000 to 65,000.
[0102] The high-hardness resins (B1) to (B5) may contain additives. As the additives, those usually used in resin sheets can be used, and examples of such additives include antioxidants, anti-coloring agents, anti-static agents, release agents, lubricants, dyes, pigments, plasticizers, flame retardants, resin modifiers, compatibilizers, and reinforcing materials such as organic fillers and inorganic fillers. The method of mixing the additives and the resin is not particularly limited, and a method of compounding the entire amount, a method of dry blending a master batch, a method of dry blending the entire amount, and the like can be used. The amount of the additive is preferably 0 to 10% by mass, more preferably 0 to 7% by mass, and particularly preferably 0 to 5% by mass, based on the total mass of the high-hardness resin layer.
[0103] The thickness of the high-hardness resin layer affects the surface hardness and impact resistance. That is, if the high-hardness resin layer is too thin, the surface hardness is low, and if it is too thick, the impact resistance is reduced. The thickness of the high-hardness resin layer is preferably 10 to 250 μm, more preferably 30 to 200 μm, and particularly preferably 60 to 150 μm.
[0104] Although there may be an additional layer between the polycarbonate layer and the high hardness resin layer, here, the case where the high hardness resin layer is laminated on the substrate layer will be described. The lamination method is not particularly limited, and can be laminated in the same manner even when other layers are present. For example, there are various methods such as a method of overlapping a substrate layer and a high hardness resin layer formed separately and heating and pressing them together; a method of overlapping a substrate layer and a high hardness resin layer formed separately and bonding them together with an adhesive; a method of co-extrusion molding a substrate layer and a high hardness resin layer; a method of in-mold molding a substrate layer into a high hardness resin layer formed in advance to integrate them. Among these, the co-extrusion molding method is preferable from the viewpoint of manufacturing cost and productivity.
[0105] The method of co-extrusion is not particularly limited. For example, in the feed block method, a high-hardness resin layer is arranged on one side of a base layer in a feed block, extruded into a sheet shape with a T-die, and then cooled while passing through a forming roll to form a desired laminate. In the multi-manifold method, a high-hardness resin layer is arranged on one side of a base layer in a multi-manifold die, extruded into a sheet shape, and then cooled while passing through a forming roll to form a desired laminate.
[0106] The total thickness of the base layer and the high-hardness resin layer is preferably 100 to 3,000 μm, more preferably 500 to 3,000 μm, and particularly preferably 1,000 to 3,000 μm. By making the total thickness 100 μm or more, the rigidity of the sheet can be maintained. Furthermore, by making the total thickness 3,000 μm or less, it is possible to prevent the sensitivity of the touch sensor from being deteriorated when a touch panel is installed under the sheet. The ratio of the thickness of the base layer to the total thickness of the base layer and the high-hardness resin layer is preferably 75% to 99%, more preferably 80 to 99%, and particularly preferably 85 to 99%. By making it within the above range, both hardness and impact resistance can be achieved.
[0107] (Hard coat layer) The antiglare laminate (resin sheet) of the present invention includes a hard coat layer. An additional layer may be present between the hard coat layer and the high-hardness resin layer, but preferably, the hard coat layer is laminated on the high-hardness resin layer. The hard coat layer is preferably an acrylic hard coat. In this specification, the term "acrylic hard coat" refers to a coating film formed by polymerizing a monomer, oligomer, or prepolymer containing a (meth)acryloyl group as a polymerizable group to form a crosslinked structure. The composition of the acrylic hard coat preferably includes 2 to 98% by mass of a (meth)acrylic monomer, 2 to 98% by mass of a (meth)acrylic oligomer, and 0 to 15% by mass of a surface modifier, and further preferably includes 0.001 to 7 parts by mass of a photopolymerization initiator relative to 100 parts by mass of the total of the (meth)acrylic monomer, the (meth)acrylic oligomer, and the surface modifier.
[0108] The hard coat layer more preferably contains 5 to 50 mass% of a (meth)acrylic monomer, 50 to 95 mass% of a (meth)acrylic oligomer, and 1 to 10 mass% of a surface modifier, and particularly preferably contains 20 to 40 mass% of a (meth)acrylic monomer, 60 to 80 mass% of a (meth)acrylic oligomer, and 2 to 5 mass% of a surface modifier.
[0109] The amount of the photopolymerization initiator is more preferably 0.01 to 5 parts by mass, and particularly preferably 0.1 to 3 parts by mass, per 100 parts by mass of the total of the (meth)acrylic monomer, (meth)acrylic oligomer, and surface modifier.
[0110] (1) (Meth)acrylic monomers As the (meth)acrylic monomer, any monomer having a (meth)acryloyl group as a functional group in the molecule can be used, and it may be a monofunctional monomer, a difunctional monomer, or a trifunctional or higher functional monomer.
[0111] Examples of monofunctional monomers include (meth)acrylic acid and (meth)acrylic acid esters. Specific examples of difunctional and / or trifunctional or higher (meth)acrylic monomers include diethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, bisphenol A diglycidyl ether di(meth)acrylate, tetraethylene glycol di(meth)acrylate, hydroxypivalic acid neopentyl glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,4-butanediol diacrylate, 1,3-butylene glycol di(meth)acrylate, dicyclopentanyl di(meth)acrylate, ) acrylate, polyethylene glycol diacrylate, 1,4-butanediol oligoacrylate, neopentyl glycol oligoacrylate, 1,6-hexanediol oligoacrylate, trimethylolpropane tri(meth)acrylate, trimethylolpropane ethoxy tri(meth)acrylate, trimethylolpropane propoxy tri(meth)acrylate, pentaerythritol tri(meth)acrylate, glyceryl propoxy tri(meth)acrylate, trimethylolpropane trimethacrylate, trimethylolpropane ethylene oxide adduct triacrylate, glycerin propylene oxide adduct triacrylate, pentaerythritol tetraacrylate, etc. can be exemplified, but are not limited to these.
[0112] The hard coat layer may contain one or more types of (meth)acrylic monomers.
[0113] (2) (Meth)acrylic oligomer Examples of the (meth)acrylic oligomer include a difunctional or higher polyfunctional urethane (meth)acrylate oligomer (hereinafter also referred to as a "polyfunctional urethane (meth)acrylate oligomer"), a difunctional or higher polyfunctional polyester (meth)acrylate oligomer (hereinafter also referred to as a "polyfunctional polyester (meth)acrylate oligomer"), a difunctional or higher polyfunctional epoxy (meth)acrylate oligomer (hereinafter also referred to as a "polyfunctional epoxy (meth)acrylate oligomer"), etc. The hard coat layer may contain one or more types of (meth)acrylic oligomers.
[0114] Examples of polyfunctional urethane (meth)acrylate oligomers include urethane reaction products between a (meth)acrylate monomer having at least one (meth)acryloyloxy group and a hydroxyl group in one molecule and a polyisocyanate; and urethane reaction products between an isocyanate compound obtained by reacting a polyol with a polyisocyanate and a (meth)acrylate monomer having at least one (meth)acryloyloxy group and a hydroxyl group in one molecule.
[0115] Examples of the (meth)acrylate monomer having at least one (meth)acryloyloxy group and one hydroxyl group in one molecule used in the urethanization reaction include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, glycerin di(meth)acrylate, trimethylolpropane di(meth)acrylate, pentaerythritol tri(meth)acrylate, and dipentaerythritol penta(meth)acrylate.
[0116] Examples of polyisocyanates used in the urethanization reaction include hexamethylene diisocyanate, lysine diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate, tolylene diisocyanate, xylylene diisocyanate, diisocyanates obtained by hydrogenating aromatic isocyanates among these diisocyanates (e.g., diisocyanates such as hydrogenated tolylene diisocyanate and hydrogenated xylylene diisocyanate), di- or tri-polyisocyanates such as triphenylmethane triisocyanate and dimethylene triphenyl triisocyanate, and polyisocyanates obtained by polymerizing diisocyanates.
[0117] Polyols used in the urethanization reaction generally include aromatic, aliphatic and alicyclic polyols, as well as polyester polyols, polyether polyols, etc. Typical aliphatic and alicyclic polyols include 1,4-butanediol, 1,6-hexanediol, neopentyl glycol, ethylene glycol, propylene glycol, trimethylolethane, trimethylolpropane, dimethylolheptane, dimethylolpropionic acid, dimethylolbutyric acid, glycerin, hydrogenated bisphenol A, etc.
[0118] The polyester polyol may be one obtained by the dehydration condensation reaction of the above-mentioned polyols and polycarboxylic acid. Specific examples of the polycarboxylic acid include succinic acid, adipic acid, maleic acid, trimellitic acid, hexahydrophthalic acid, phthalic acid, isophthalic acid, and terephthalic acid. These polycarboxylic acids may be anhydrides. In addition to polyalkylene glycol, the polyether polyol may be one obtained by the reaction of the above-mentioned polyols or phenols with alkylene oxide.
[0119] Also, the multifunctional polyester (meth)acrylate oligomer is obtained by a dehydration condensation reaction using (meth)acrylic acid, a polycarboxylic acid, and a polyol. Examples of the polycarboxylic acid used in the dehydration condensation reaction include succinic acid, adipic acid, maleic acid, itaconic acid, trimellitic acid, pyromellitic acid, hexahydrophthalic acid, phthalic acid, isophthalic acid, and terephthalic acid. These polycarboxylic acids may be anhydrides. Examples of the polyol used in the dehydration condensation reaction include 1,4-butanediol, 1,6-hexanediol, diethylene glycol, triethylene glycol, propylene glycol, neopentyl glycol, dimethylolheptane, dimethylolpropionic acid, dimethylolbutyric acid, trimethylolpropane, ditrimethylolpropane, pentaerythritol, and dipentaerythritol.
[0120] Multifunctional epoxy (meth)acrylate oligomers are obtained by addition reaction of polyglycidyl ethers with (meth)acrylic acid. Examples of polyglycidyl ethers include ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, tripropylene glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, and bisphenol A diglycidyl ether.
[0121] (3) Modifier The modifiers used in the present invention are agents that change the performance of the hard coat layer, such as leveling agents, antistatic agents, surfactants, water and oil repellents, and UV absorbers.
[0122] Examples of the leveling agent include polyether-modified polyalkylsiloxane, polyether-modified siloxane, polyester-modified hydroxyl-containing polyalkylsiloxane, polyether-modified polydimethylsiloxane having an alkyl group, modified polyether, and silicon-modified acrylic.
[0123] Examples of the antistatic agent include glycerin fatty acid ester monoglycerides, glycerin fatty acid ester organic acid monoglycerides, polyglycerin fatty acid esters, sorbitan fatty acid esters, cationic surfactants, and anionic surfactants.
[0124] Examples of surfactants and water- and oil-repellents include fluorine-containing surfactants and water- and oil-repellents such as oligomers containing a fluorine-containing group and a lipophilic group, and oligomers containing a fluorine-containing group, a hydrophilic group, a lipophilic group, and a UV-reactive group.
[0125] Examples of UV absorbents include hydroxyphenyltriazines, benzotriazoles, and benzophenones.
[0126] The hard coat layer may contain a photopolymerization initiator. In this specification, the photopolymerization initiator refers to a photoradical generator.
[0127] Examples of monofunctional photopolymerization initiators that can be used in the present invention include 4-(2-hydroxyethoxy)phenyl(2-hydroxy-2-propyl)ketone [Darocure 2959: manufactured by Merck]; α-hydroxy-α,α'-dimethylacetophenone [Darocure 1173: manufactured by Merck]; acetophenone-based initiators such as methoxyacetophenone, 2,2'-dimethoxy-2-phenylacetophenone [Irgacure 651], and 1-hydroxy-cyclohexyl phenyl ketone; benzoin ether-based initiators such as benzoin ethyl ether and benzoin isopropyl ether; and other halogenated ketones, acylphosphinoxides, and acylphosphonates.
[0128] The method for forming the hard coat layer is not particularly limited. For example, the hard coat layer can be formed by applying a hard coat liquid onto a layer (e.g., a high-hardness resin layer) located below the hard coat layer, and then photopolymerizing the hard coat layer.
[0129] The method for applying the hard coat coating material in the present invention is not particularly limited, and any known method can be used, such as spin coating, dipping, spraying, slide coating, bar coating, roll coating, gravure coating, meniscus coating, flexographic printing, screen printing, beat coating, and brushing.
[0130] Lamps used for light irradiation in photopolymerization are those having an emission distribution at a light wavelength of 420 nm or less, examples of which include low-pressure mercury lamps, medium-pressure mercury lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, chemical lamps, black light lamps, microwave-excited mercury lamps, metal halide lamps, etc. Among these, high-pressure mercury lamps and metal halide lamps are preferred because they efficiently emit light in the active wavelength region of the initiator and do not emit much short-wavelength light that reduces the viscoelastic properties of the resulting polymer due to crosslinking, or long-wavelength light that heats and evaporates the reaction composition.
[0131] The irradiation intensity of the lamp is a factor that determines the degree of polymerization of the resulting polymer, and is appropriately controlled for each performance of the target product. When a typical cleavage-type initiator having an acetophenone group is blended, the illuminance is 0.1 to 300 mW / cm 2 In particular, a metal halide lamp is used, and the illuminance is set to 10 to 40 mW / cm. 2 It is preferable to set the above.
[0132] Photopolymerization reaction is inhibited by oxygen in air or oxygen dissolved in the reactive composition. Therefore, it is desirable to carry out light irradiation using a method that can eliminate reaction inhibition by oxygen. One such method is a method in which the reactive composition is covered with a film made of polyethylene terephthalate or Teflon to prevent contact with oxygen, and light is irradiated to the reactive composition through the film. In addition, light may be irradiated to the composition through a light-transmitting window in an inert atmosphere in which oxygen is replaced with an inert gas such as nitrogen gas or carbon dioxide gas.
[0133] When the light irradiation is performed under an inert atmosphere, a certain amount of inert gas is always introduced to keep the oxygen concentration of the atmosphere at a low level. The introduction of this inert gas generates an airflow on the surface of the reactive composition, causing monomer evaporation. In order to suppress the level of monomer evaporation, the airflow speed of the inert gas is preferably 1 m / sec or less, more preferably 0.1 m / sec or less, as a relative speed to the laminate coated with the hard coat liquid moving under the inert gas atmosphere. By setting the airflow speed within the above range, monomer evaporation due to airflow is substantially suppressed.
[0134] In order to improve the adhesion of the hard coat layer, the coated surface may be pretreated by known methods such as sandblasting, solvent treatment, corona discharge treatment, chromic acid treatment, flame treatment, hot air treatment, ozone treatment, ultraviolet treatment, and primer treatment using a resin composition.
[0135] The hard coat layer is exposed to UV light (254 nm) with an irradiation output of 20 mW / cm 2 When irradiated with ultraviolet light using a metal halide lamp, it is preferable that the pencil hardness is 2H or more.
[0136] The thickness of the hard coat layer is preferably 1 μm or more and 40 μm or less, more preferably 2 μm or more and 10 μm or less. A thickness of 1 μm or more can provide sufficient hardness. A thickness of 40 μm or less can suppress the occurrence of cracks during bending. The thickness of the hard coat layer can be measured by observing the cross section with a microscope or the like and measuring from the coating interface to the surface.
[0137] In one embodiment of the present invention, the hard coat layer having a concave-convex shape may have at least one of anti-reflection performance, antifouling performance, antistatic performance, and weather resistance. The method of subjecting the hard coat layer to anti-reflection treatment, antifouling treatment, antistatic treatment, weather resistance treatment, and other treatments is not particularly limited, and known methods can be used. For example, a method of applying a reflection reducing paint, a method of depositing a dielectric thin film, a method of applying an antistatic paint, and the like can be mentioned.
[0138] The method of forming the unevenness on the hard coat layer includes, for example, molding using a mold. Molding using a mold can be performed by preparing a mold having a shape complementary to the uneven surface, and then in a state where a transparent substrate coated with a hard coat is closely attached to the mold, followed by ultraviolet curing.
[0139] One method for evaluating character blur is the transmitted image clarity (transmitted clarity) based on JIS K 7374. The optical comb widths are 0.125 mm, 0.25 mm, 0.5 mm, 1.0 mm, and 2.0 mm. A narrower optical comb width results in a larger variation in the values, whereas a wider optical comb width results in a smaller variation in the values. Therefore, the optical comb width of 2.0 mm is preferable.
[0140] The larger the transmission clarity value, the more suppressed the blurring of characters is, and the smaller the value, the more blurring of characters occurs. Note that, in the present invention, the transmission clarity can be measured by the method described in the examples described later.
[0141] One method for evaluating image reflection is the image clarity of reflection (reflection clarity) measured at a light incidence angle of 45° based on JIS K 7374. The optical comb widths are 0.125 mm, 0.25 mm, 0.5 mm, 1.0 mm, and 2.0 mm. A narrower optical comb width results in a larger variation in values, whereas a wider optical comb width results in a smaller variation in values. Therefore, the optical comb width of 2.0 mm is preferred.
[0142] The reflection clarity measured at a light incidence angle of 45° indicates that the larger the value, the easier it is for an image to be reflected, and the smaller the value, the less likely it is for an image to be reflected. In the present invention, the reflection clarity can be measured by the method described in the examples below.
[0143] In the present invention, in order to achieve both blurred characters and image reflection performance, the transmission clarity when light is transmitted through an optical comb having a width of 2.0 mm is defined as T1, and the reflection clarity measured at an incident angle of 45° using an optical comb having a width of 2.0 mm is defined as T2, so that T1 / T2 is preferably 2.0 or more, more preferably 3.0 or more, and particularly preferably 3.0 to 4.0. The reflection clarity can be measured by applying black tape to the back surface of the uneven surface to suppress back reflection.
[0144] It is preferable that the transmission clarity T1 when light is transmitted using an optical comb with a width of 2.0 mm satisfies 30%≦T1≦50%, and more preferably satisfies 40%≦T1≦50%, and it is preferable that the reflection clarity T2 measured using an optical comb with a width of 2.0 mm at a light incidence angle of 45° satisfies 10%≦T2≦20%, and more preferably satisfies 10%≦T2≦15%.
[0145] In the present invention, the hard coat layer having a concave-convex shape preferably does not contain inorganic particles or organic particles. The concave-convex shape in the present invention is provided by transfer. In this way, by not containing inorganic particles or organic particles in the hard coat layer, scratch resistance can be improved. In the present invention, a second hard coat layer may be provided on the opposite side to the hard coat layer having concave-convex shapes. In a preferred embodiment of the present invention, the second hard coat layer has at least one of anti-reflection performance, antifouling performance, antistatic performance, and weather resistance.
[0146] Another embodiment of the present invention provides a method for manufacturing the antiglare laminate, which includes a step of transferring an uneven shape to the hard coat layer by pressing a patterned PET film onto a photocurable resin composition on a layer containing a high-hardness resin (B). As the patterned PET film, for example, PTH, PTHA, or PTHZ of Emblet manufactured by Unitika, PF11 or PF23 of low-glare AG film manufactured by Daicel, etc. can be used.
Examples
[0147] Examples of the present invention are shown below, but the present invention is not limited to the embodiments of the examples.
[0148] <Transmission clarity (T1)> Using "ICM 1T" manufactured by Suga Test Instruments Co., Ltd., based on JIS K7374, measurement was carried out with the flow direction of the antiglare laminate and the direction of the teeth of the optical comb being parallel. Among the optical combs, the clarity transmitted from the light source using an optical comb with a width of 2.0 mm was defined as the transmission clarity.
[0149] <Reflection clarity (T2)> Using "ICM 1T" manufactured by Suga Test Instruments Co., Ltd., based on JIS K7374, measurement was carried out with the flow direction of the antiglare laminate and the direction of the teeth of the optical comb being parallel. Among the optical combs, the image clarity of the reflection measured at an incident angle of 45° of light using an optical comb with a width of 2.0 mm was defined as the reflection clarity. Measurement was carried out by suppressing the back reflection by attaching a black tape (black vinyl tape model number 117BLA manufactured by 3M Japan Limited) to the back surface of the uneven surface.
[0150] <SW hardness> For the antiglare laminate, using steel wool #0000 manufactured by Nippon Steel Wool Co., Ltd., the degree of scratching when reciprocated 15 times under a load of 100 g / cm 2 was visually observed and evaluated on a 10-point scale. It was described as RANK1~RANK10. RANK1: No scratch (similar to inorganic glass) RANK10: Many scratches (similar to polycarbonate)
[0151] <Shape stability> A test piece was cut to 100 mm x 60 mm. The cut test piece was set in a two-point support holder and placed in an environmental tester set at a temperature of 23% and a relative humidity of 50% for more than 24 hours to condition it, and then the warpage was measured (before treatment). Next, the test piece was set in the holder and placed in an environmental tester set at a temperature of 85°C and a relative humidity of 85%, and held in that state for 120 hours. The holder was then moved into an environmental tester set at a temperature of 23% and a relative humidity of 50%, and after holding in that state for 4 hours, the warpage was measured again (after treatment). The warpage was measured using a three-dimensional shape measuring machine (KEYENCE KS-1000) equipped with an electric stage, and the taken test piece was placed horizontally in an upward convex position, scanned at 1 mm intervals, and the bulge in the center was measured as the warpage. The absolute value of the difference in the amount of warpage before and after treatment, i.e. |(Warpage after processing)-(Warpage before processing)| was evaluated as shape stability.
[0152] Example 1 <Laminate (X-1)> A synthetic resin laminate was formed using a multi-layer extrusion device having a single screw extruder with a shaft diameter of 35 mm, a single screw extruder with a shaft diameter of 65 mm, a feed block connected to all the extruders, and a T-die connected to the feed block. Mitsubishi Gas Chemical's Optimas 7500 was continuously introduced as the high-hardness resin (B1) into the single screw extruder with a shaft diameter of 35 mm, and extruded under the conditions of a cylinder temperature of 240°C and a discharge rate of 2.6 kg / h. Polycarbonate resin (manufactured by Mitsubishi Engineering Plastics Corporation, product name: Iupilon S-1000) was continuously introduced into the single screw extruder with a shaft diameter of 65 mm, and extruded at a cylinder temperature of 280°C and a discharge rate of 50.0 kg / h. The feed block connected to all the extruders was equipped with two-type, two-layer distribution pins, and the high-hardness resin (B1) and polycarbonate resin were introduced and laminated at a temperature of 270°C. The extruded material was extruded into a sheet shape through a T-die connected to the upstream at a temperature of 270°C, and cooled while transferring a mirror surface with three mirror-finishing rolls whose temperatures were set at 120°C, 130°C, and 190°C from the upstream side, to obtain a laminate (X-1) of a high-hardness resin (B1) layer and a polycarbonate resin layer. The thickness of the obtained laminate (X-1) was 1.0 mm, and the thickness of the high-hardness resin (B1) layer was 60 μm near the center. The Optimas 7500 manufactured by Mitsubishi Gas Chemical Company, used as the high hardness resin (B1), is a copolymer resin containing the (meth)acrylic acid ester constituent unit (a) represented by the general formula (1) above and the aliphatic vinyl constituent unit (b) represented by the general formula (2) above, in which the total proportion of the (meth)acrylic acid ester constituent unit (a) and the aliphatic vinyl constituent unit (b) is 99 mol % of all constituent units of the copolymer resin, and the proportion of the (meth)acrylic acid ester constituent unit (a) is 75 mol % of all constituent units of the copolymer resin.
[0153] <Photocurable resin composition (Y-1)> U6HA: 60% by mass of hexafunctional urethane acrylate oligomer (manufactured by Shin-Nakamura Chemical Co., Ltd.), #260: 35% by mass of 1,9-nonanediol diacrylate (Osaka Organic Chemical Industry Co., Ltd.), A mixture of 5% by mass of fluorine-based leveling agent is used as 100 parts by mass. Photoinitiator: 3 parts by mass of I-184 (manufactured by BASF Ltd. [compound name: 1-hydroxy-cyclohexyl phenyl ketone]) was added to obtain a photocurable resin composition (Y-1).
[0154] <Patterned PET film (Z-1)> The PET film used for transferring the uneven shape was C-50 G-100-1 manufactured by Nakajima Kogyo Co., Ltd.
[0155] A photocurable resin composition (Y-1) was applied to the high-hardness resin (B1) layer of the laminate (X-1) using a bar coater so that the thickness of the coating after curing would be 5 to 10 μm, and the patterned PET film (Z-1) was covered and pressed so that the patterned surface of the film would come into contact with the coating liquid. Then, the film was cured by irradiating a metal halide lamp (20 mW / cm) from a light source distance of 12 cm for 30 seconds, and the patterned PET film was peeled off to obtain an antiglare laminate having an uneven hard coat layer on the high-hardness resin (B1) layer.
[0156] Example 2 An antiglare laminate was obtained in the same manner as in Example 1, except that C-50 G-100-2 (Z-2) manufactured by Nakajima Kogyo Co., Ltd. was used as the patterned PET film.
[0157] Example 3 An antiglare laminate was obtained in the same manner as in Example 1, except that C-50 G-100-3 (Z-3) manufactured by Nakajima Kogyo Co., Ltd. was used as the patterned PET film.
[0158] Example 4 <Production of high hardness resin (B2)> 40% by mass of the high hardness resin (B1) used in Example 1 and 60% by mass of XIBOND140 manufactured by POLYSCOPE POLYMERS BV as a styrene-unsaturated dicarboxylic acid copolymer (C) were charged, mixed in a blender for 30 minutes, and then melt-kneaded at a cylinder temperature of 230°C using an extruder with a screw diameter of 26 mm (Toshiba Machine, TEM-26SS, L / D ≒ 40), extruded into a strand shape, and pelletized with a pelletizer to obtain a high hardness resin (B2). Pelletization was performed stably. The styrene-unsaturated dicarboxylic acid copolymer (C) used was XIBOND140 manufactured by POLYSCOPE POLYMERS BV, which is a resin containing 85% by mass of styrene monomer units (c1) and 15% by mass of unsaturated dicarboxylic acid anhydride monomer units (c2).
[0159] <Laminate (X-2)> A synthetic resin laminate was formed using a multi-layer extrusion device having a single screw extruder with a shaft diameter of 35 mm, a single screw extruder with a shaft diameter of 65 mm, a feed block connected to all the extruders, and a T-die connected to the feed block. A high-hardness resin (B2) was continuously introduced into the single screw extruder with a shaft diameter of 35 mm, and extruded under the conditions of a cylinder temperature of 240°C and a discharge rate of 2.6 kg / h. A polycarbonate resin (manufactured by Mitsubishi Engineering Plastics Corporation, product name: Iupilon S-1000) was continuously introduced into the single screw extruder with a shaft diameter of 65 mm, and extruded at a cylinder temperature of 280°C and a discharge rate of 50.0 kg / h. The feed block connected to all the extruders was equipped with a two-type two-layer distribution pin, and the high-hardness resin (B2) and the polycarbonate resin were introduced and laminated at a temperature of 270°C. The extruded material was extruded into a sheet shape through a T-die connected ahead at a temperature of 270°C, and cooled while transferring a mirror surface through three mirror-finishing rolls whose temperatures were set from the upstream side to 120°C, 130°C, and 190°C, yielding a laminate (X-2) of a high-hardness resin (B2) layer and a polycarbonate resin layer. The thickness of the resulting laminate (X-2) was 1.0 mm, and the thickness of the high-hardness resin (B2) layer was 60 μm near the center.
[0160] The photocurable resin composition (Y-1) was applied to the high hardness resin (B2) layer of the laminate (X-2) using a bar coater so that the thickness of the coating after curing would be 5 to 10 μm, and the patterned PET film (Z-1) was covered and pressed so that the patterned surface of the film would come into contact with the coating liquid. Then, the film was cured by irradiating with a metal halide lamp (20 mW / cm) from a light source distance of 12 cm for 30 seconds, and the patterned PET film was peeled off to obtain an antiglare laminate having an uneven hard coat layer on the high hardness resin (B2) layer.
[0161] Example 5 <Production of high hardness resin (B3)> 75% by mass of Resisfy R100 (manufactured by Denka) as a styrene-unsaturated dicarboxylic acid copolymer (E) and 25% by mass of methyl methacrylate resin Parapet HR-L (manufactured by Kuraray, weight average molecular weight: 90,000) as a resin containing vinyl monomer (D) were charged and mixed in a blender for 30 minutes, then melt-kneaded at a cylinder temperature of 230°C using an extruder with a screw diameter of 26 mm (manufactured by Toshiba Machine, TEM-26SS, L / D ≒ 40), extruded into strands, and pelletized with a pelletizer to obtain a high-hardness resin (B3). Pelletization was performed stably. The styrene-unsaturated dicarboxylic acid copolymer (E) used was Resistify R100 (manufactured by Denka), which is a copolymer containing 21% by mass of methyl methacrylate structural units, 64% by mass of styrene structural units, and 15% by mass of maleic anhydride structural units.
[0162] <Laminate (X-3)> A synthetic resin laminate was formed using a multi-layer extrusion device having a single screw extruder with a shaft diameter of 35 mm, a single screw extruder with a shaft diameter of 65 mm, a feed block connected to all the extruders, and a T-die connected to the feed block. A high-hardness resin (B3) was continuously introduced into the single screw extruder with a shaft diameter of 35 mm, and extruded under the conditions of a cylinder temperature of 240°C and a discharge rate of 2.6 kg / h. A polycarbonate resin (manufactured by Mitsubishi Engineering Plastics Corporation, product name: Iupilon S-1000) was continuously introduced into the single screw extruder with a shaft diameter of 65 mm, and extruded at a cylinder temperature of 280°C and a discharge rate of 50.0 kg / h. The feed block connected to all the extruders was equipped with a two-type two-layer distribution pin, and the high-hardness resin (B3) and the polycarbonate resin were introduced and laminated at a temperature of 270°C. The extruded material was extruded into a sheet shape through a T-die connected to the upstream at a temperature of 270°C, and cooled while transferring a mirror surface with three mirror-finishing rolls whose temperatures were set at 120°C, 130°C, and 190°C from the upstream side, to obtain a laminate (X-3) of a high-hardness resin (B3) layer and a polycarbonate resin layer. The thickness of the obtained laminate (X-3) was 1.0 mm, and the thickness of the high-hardness resin (B3) layer was 60 μm near the center.
[0163] The photocurable resin composition (Y-1) was applied to the high hardness resin (B3) layer of the laminate (X-3) using a bar coater so that the thickness of the coating after curing would be 5 to 10 μm, and the patterned PET film (Z-1) was covered and pressed so that the patterned surface of the film would come into contact with the coating liquid. Then, the film was cured by irradiating with a metal halide lamp (20 mW / cm) from a light source distance of 12 cm for 30 seconds, and the patterned PET film was peeled off to obtain an antiglare laminate having an uneven hard coat layer on the high hardness resin (B3) layer.
[0164] Example 6 <Production of high hardness resin (B4)> 75% by mass of the styrene-unsaturated dicarboxylic acid copolymer (E) used in Example 5 and 25% by mass of Delpet PM-120N (manufactured by Asahi Kasei Chemical Co., Ltd.), a copolymer of 7% by mass of styrene structural unit, 86% by mass of methyl methacrylate structural unit, and 7% by mass of N-phenylmaleimide structural unit, were charged as the resin copolymer (G), and mixed with a blender for 30 minutes. Then, using an extruder with a screw diameter of 26 mm (manufactured by Toshiba Machine Co., Ltd., TEM-26SS, L / D≒40), the mixture was melt-kneaded at a cylinder temperature of 230°C, extruded into a strand shape, and pelletized with a pelletizer to obtain a high-hardness resin (B4). The pelletization was performed stably.
[0165] <Laminate (X-4)> A synthetic resin laminate was formed using a multi-layer extrusion device having a single screw extruder with a shaft diameter of 35 mm, a single screw extruder with a shaft diameter of 65 mm, a feed block connected to all the extruders, and a T-die connected to the feed block. A high-hardness resin (B4) was continuously introduced into the single screw extruder with a shaft diameter of 35 mm, and extruded under the conditions of a cylinder temperature of 240°C and a discharge rate of 2.6 kg / h. A polycarbonate resin (manufactured by Mitsubishi Engineering Plastics Corporation, product name: Iupilon S-1000) was continuously introduced into the single screw extruder with a shaft diameter of 65 mm, and extruded at a cylinder temperature of 280°C and a discharge rate of 50.0 kg / h. The feed block connected to all the extruders was equipped with a two-type two-layer distribution pin, and the high-hardness resin (B4) and the polycarbonate resin were introduced and laminated at a temperature of 270°C. The extruded material was extruded into a sheet shape through a T-die connected ahead at a temperature of 270°C, and cooled while transferring a mirror surface through three mirror-finishing rolls whose temperatures were set from the upstream side to 120°C, 130°C, and 190°C, yielding a laminate (X-4) of a high-hardness resin (B4) layer and a polycarbonate resin layer. The thickness of the resulting laminate (X-4) was 1.0 mm, and the thickness of the high-hardness resin (B4) layer was 60 μm near the center.
[0166] The photocurable resin composition (Y-1) was applied to the high hardness resin (B4) layer of the laminate (X-4) using a bar coater so that the thickness of the coating after curing would be 5 to 10 μm, and the patterned PET film (Z-1) was covered and pressed so that the patterned surface of the film would come into contact with the coating liquid. Then, the film was cured by irradiating with a metal halide lamp (20 mW / cm) from a light source distance of 12 cm for 30 seconds, and the patterned PET film was peeled off to obtain an antiglare laminate having an uneven hard coat layer on the high hardness resin (B4) layer.
[0167] Example 7 <Laminate (X-5)> A synthetic resin laminate was formed using a multi-layer extrusion device having a single screw extruder with a shaft diameter of 35 mm, a single screw extruder with a shaft diameter of 65 mm, a feed block connected to all the extruders, and a T-die connected to the feed block. Iupilon KH3410UR (manufactured by Mitsubishi Engineering Plastics) was continuously introduced as a high-hardness resin (B5) into the single screw extruder with a shaft diameter of 35 mm, and extruded under the conditions of a cylinder temperature of 270°C and a discharge rate of 2.6 kg / h. Polycarbonate resin (manufactured by Mitsubishi Engineering Plastics, trade name: Iupilon S-1000) was continuously introduced into the single screw extruder with a shaft diameter of 65 mm, and extruded at a cylinder temperature of 280°C and a discharge rate of 50.0 kg / h. The feed block connected to all the extruders was equipped with a two-type two-layer distribution pin, and the high-hardness resin (B5) and polycarbonate resin were introduced and laminated at a temperature of 270°C. The extruded material was extruded into a sheet shape through a T-die connected to the upstream at a temperature of 270°C, and cooled while transferring a mirror surface through three mirror-finishing rolls whose temperatures were set to 120°C, 130°C, and 190°C from the upstream side, to obtain a laminate (X-5) of a high-hardness resin (B5) layer and a polycarbonate resin layer. The thickness of the obtained laminate (X-5) was 1.0 mm, and the thickness of the high-hardness resin (B5) layer was 60 μm near the center.
[0168] The photocurable resin composition (Y-1) was applied to the high hardness resin (B5) layer of the laminate (X-5) using a bar coater so that the coating thickness after curing would be 5 to 10 μm, and the patterned PET film (Z-1) was covered and pressed so that the patterned surface of the film would come into contact with the coating liquid. Then, the film was cured by irradiating with a metal halide lamp (20 mW / cm) from a light source distance of 12 cm for 30 seconds, and the patterned PET film was peeled off to obtain an antiglare laminate having an uneven hard coat layer on the high hardness resin (B5) layer.
[0169] Comparative Example 1 An antiglare laminate was obtained in the same manner as in Example 1, except that PS-27 (Z-4) manufactured by Daicel was used as the patterned PET film.
[0170] Comparative Example 2 Coating liquid (i) was prepared by mixing and stirring 50 parts by mass of MEK, 50 parts by mass of an acrylic ultraviolet-curing resin (100% solids, product name: Light Acrylate DPE-6A, manufactured by Kyoeisha Chemical Co., Ltd.), 0.5 parts by mass of silica fine particles (octylsilane-treated fumed silica, average primary particle diameter 12 nm, manufactured by Nippon Aerosil Co., Ltd.), 1 part by mass of an acrylic silane-treated silica (average particle diameter 1.9 μm, product name: SE-6050-SYB, manufactured by Admatechs Co., Ltd.), and 3 parts by mass of a photoinitiator (product name: Omnirad184IGM Resins). Next, the coating liquid (i) was applied to a PET (polyethylene terephthalate) film to a dry film thickness of 2.5 μm, and the coating liquid was dried at 80° C. for 2 minutes. The coating liquid was then cured by irradiating the film with ultraviolet light at a line speed of 1.5 m / min using a conveyor equipped with a high-pressure mercury lamp having a light source distance of 12 cm and an output of 80 W / cm. An antiglare laminate was obtained in the same manner as in Example 1, except that a patterned PET film (Z-5) was used.
[0171] Comparative Example 3 50% by mass of MEK, 50 parts by mass of acrylic ultraviolet curing resin (100% solid content product: Light Acrylate DPE-6A, manufactured by Kyoeisha Chemical Co., Ltd.), 1.5 parts by mass of silica fine particles (octylsilane-treated fumed silica, average primary particle diameter 1.9 μm, product name: SE6050-SYB, manufactured by Admatechs Co., Ltd.), and 3 parts by mass of photoinitiator (product name Irgacure 184, manufactured by Toyota Tsusho Chemiplas Co., Ltd.) were mixed and stirred to prepare a coating liquid (Y-2). The coating liquid (Y-2) was applied to the laminate (X-1) described in Example 1 so that the dry film thickness was 2.5 μm, and after drying at 80 ° C. for 2 minutes, it was irradiated with a metal halide lamp (20 mW / cm) for 30 seconds while purging with nitrogen to cure, thereby obtaining an antiglare laminate.
[0172] Comparative Example 4 A hard coat layer was formed in the same manner as in Example 1, except that a laminate (X-6) obtained by using methyl methacrylate resin Parapet HR-L (manufactured by Kuraray, weight average molecular weight: 90,000) instead of the high hardness resin (B1) was used, and an antiglare laminate was obtained.
[0173] The antiglare laminates obtained in Examples 1 to 7 and Comparative Examples 1 to 4 were evaluated for transmitted light clarity, 45° reflected light clarity, SW hardness, and shape stability. The results are shown in the table below. [Table 1]
[0174] As described above, it has been found that the present invention provides an antiglare laminate having antiglare properties that combine anti-reflection performance and suppression of character blurring, while also having high scratch resistance and excellent shape stability.
Claims
1. A layer containing a resin (A) containing a polycarbonate resin (a1); a layer containing a high-hardness resin (B) provided on at least one surface of a layer containing a resin (A) containing a polycarbonate resin (a1); a hard coat layer having an uneven shape and provided on the layer containing a high-hardness resin (B); A touch panel front protection plate comprising an antiglare laminate satisfying the following conditions (i) and (ii): (i) the thickness of the layer containing the high-hardness resin (B) is 10 to 250 μm, and the total thickness of the layer containing the resin (A) including the polycarbonate resin (a1) and the layer containing the high-hardness resin (B) is 100 to 3,000 μm; (ii) the laminate has a T1 / T2 ratio of 2.0 or more, where T1 is the transmitted clarity when light is transmitted through an optical comb having a width of 2.0 mm, and T2 is the reflected clarity measured at an incident angle of 45° using an optical comb having a width of 2.0 mm; (iii) the transmission clarity T1 when light is transmitted using an optical comb having a width of 2.0 mm satisfies 30%≦T1≦50%, and the reflection clarity T2 measured using an optical comb having a width of 2.0 mm at an incident angle of 45° satisfies 10%≦T2≦20%, The high hardness resin (B) contains at least one selected from the group consisting of the following resins (B1) to (B5): The resin (B1) is A copolymer resin comprising a (meth)acrylic acid ester structural unit (a) represented by the following general formula (1) and an aliphatic vinyl structural unit (b) represented by the following general formula (2), wherein the total proportion of the (meth)acrylic acid ester structural unit (a) and the aliphatic vinyl structural unit (b) is 90 to 100 mol % of all structural units of the copolymer resin, and the proportion of the (meth)acrylic acid ester structural unit (a) is 65 to 80 mol % of all structural units of the copolymer resin: 【Chemistry 1】 (In the formula, R1 is a hydrogen atom or a methyl group, and R2 is an alkyl group having 1 to 18 carbon atoms.) 【Chemistry 2】 (In the formula, R3 is a hydrogen atom or a methyl group, and R4 is a cyclohexyl group which may have a hydrocarbon group having 1 to 4 carbon atoms.) and The resin (B2) is the resin (B1) is 35 to 65% by mass, and the styrene-unsaturated dicarboxylic acid copolymer (C) is 35 to 65% by mass, the styrene-unsaturated dicarboxylic acid copolymer (C) is a resin containing 65 to 90% by mass of a styrene monomer unit (c1) and 10 to 35% by mass of an unsaturated dicarboxylic anhydride monomer unit (c2); The resin (B3) is The present invention relates to a resin composition comprising: 55 to 10 mass% of a resin (D) containing a vinyl monomer; and 45 to 90 mass% of a styrene-unsaturated dicarboxylic acid copolymer (E); the styrene-unsaturated dicarboxylic acid copolymer (E) is a resin containing 50 to 80 mass% of a styrene monomer unit (e1), 10 to 30 mass% of an unsaturated dicarboxylic acid monomer unit (e2), and 5 to 30 mass% of a vinyl monomer unit (e3); The resin (B4) is a resin copolymer (G) containing 5 to 20% by mass of a styrene structural unit, 60 to 90% by mass of a (meth)acrylic acid ester structural unit, and 5 to 20% by mass of an N-substituted maleimide monomer, or an alloy of the resin copolymer (G) and the copolymer (E); The resin (B5) is A copolymer containing a structural unit (H) represented by the following formula (3) and, optionally, a structural unit (J) represented by the following formula (4): 【Chemistry 3】 【Chemistry 4】 The hard coat layer having a concave-convex shape does not contain inorganic particles or organic particles. The touch panel front protective plate.
2. The touch panel front protection plate according to claim 1 , wherein the hard coat layer having the uneven surface has at least one of anti-reflection properties, anti-fouling properties, anti-static properties, and weather resistance.
3. The touch panel front protection plate according to claim 1 , further comprising a second hard coat layer on a surface opposite to the hard coat layer having the irregularities.
4. The touch panel front protection plate according to claim 3 , wherein the second hard coat layer has at least one of anti-reflection properties, anti-fouling properties, anti-static properties, and weather resistance.
5. The touch panel front protection plate according to any one of claims 1 to 4, comprising, as the polycarbonate resin (a1), a component derived from a monohydric phenol represented by the following general formula (5): 【Chemistry 5】 (In the formula, R 1 represents an alkyl group having 8 to 36 carbon atoms or an alkenyl group having 8 to 36 carbon atoms; R 2 ~R 5 each independently represents a hydrogen atom, a halogen, or an alkyl group having 1 to 20 carbon atoms or an aryl group having 6 to 12 carbon atoms which may have a substituent, and the substituent is a halogen, an alkyl group having 1 to 20 carbon atoms, or an aryl group having 6 to 12 carbon atoms.
6. A layer comprising a resin (A) containing a polycarbonate resin (a1); a layer containing a high-hardness resin (B) provided on at least one surface of a layer containing a resin (A) containing a polycarbonate resin (a1); a hard coat layer having an uneven shape and provided on the layer containing a high-hardness resin (B); A front panel for an office automation device, a portable electronic device, or a television, comprising an antiglare laminate that satisfies the following conditions (i) and (ii): (i) the thickness of the layer containing the high-hardness resin (B) is 10 to 250 μm, and the total thickness of the layer containing the resin (A) including the polycarbonate resin (a1) and the layer containing the high-hardness resin (B) is 100 to 3,000 μm; (ii) the laminate has a T1 / T2 ratio of 2.0 or more, where T1 is the transmitted clarity when light is transmitted through an optical comb having a width of 2.0 mm, and T2 is the reflected clarity measured at an incident angle of 45° using an optical comb having a width of 2.0 mm; (iii) the transmission clarity T1 when light is transmitted using an optical comb having a width of 2.0 mm satisfies 30%≦T1≦50%, and the reflection clarity T2 measured using an optical comb having a width of 2.0 mm at an incident angle of 45° satisfies 10%≦T2≦20%, The high hardness resin (B) contains at least one selected from the group consisting of the following resins (B1) to (B5): The resin (B1) is A copolymer resin comprising a (meth)acrylic acid ester structural unit (a) represented by the following general formula (1) and an aliphatic vinyl structural unit (b) represented by the following general formula (2), wherein the total proportion of the (meth)acrylic acid ester structural unit (a) and the aliphatic vinyl structural unit (b) is 90 to 100 mol % of all structural units of the copolymer resin, and the proportion of the (meth)acrylic acid ester structural unit (a) is 65 to 80 mol % of all structural units of the copolymer resin: 【Chemistry 6】 (In the formula, R1 is a hydrogen atom or a methyl group, and R2 is an alkyl group having 1 to 18 carbon atoms.) 【Chemistry 7】 (In the formula, R3 is a hydrogen atom or a methyl group, and R4 is a cyclohexyl group which may have a hydrocarbon group having 1 to 4 carbon atoms.) and The resin (B2) is the resin (B1) is 35 to 65% by mass, and the styrene-unsaturated dicarboxylic acid copolymer (C) is 35 to 65% by mass, the styrene-unsaturated dicarboxylic acid copolymer (C) is a resin containing 65 to 90% by mass of a styrene monomer unit (c1) and 10 to 35% by mass of an unsaturated dicarboxylic anhydride monomer unit (c2); The resin (B3) is The present invention relates to a resin composition comprising: 55 to 10 mass% of a resin (D) containing a vinyl monomer; and 45 to 90 mass% of a styrene-unsaturated dicarboxylic acid copolymer (E); the styrene-unsaturated dicarboxylic acid copolymer (E) is a resin comprising 50 to 80 mass% of a styrene monomer unit (e1), 10 to 30 mass% of an unsaturated dicarboxylic acid monomer unit (e2), and 5 to 30 mass% of a vinyl monomer unit (e3); The resin (B4) is a resin copolymer (G) containing 5 to 20% by mass of a styrene structural unit, 60 to 90% by mass of a (meth)acrylic acid ester structural unit, and 5 to 20% by mass of an N-substituted maleimide monomer, or an alloy of the resin copolymer (G) and the copolymer (E); The resin (B5) is A copolymer containing a structural unit (H) represented by the following formula (3) and, optionally, a structural unit (J) represented by the following formula (4): 【Chemistry 8】 【Chemistry 9】 The hard coat layer having a concave-convex shape does not contain inorganic particles or organic particles. A front panel for the office automation equipment, portable electronic device, or television.
7. A front panel for office equipment, portable electronic devices, or televisions as described in claim 6, wherein the hard coat layer having the uneven shape has at least one of anti-reflection performance, anti-fouling performance, anti-static performance, and weather resistance.
8. A front panel for office automation equipment, portable electronic devices, or televisions as described in claim 6 or 7, comprising a second hard coat layer on the side opposite to the hard coat layer having the unevenness.
9. A front panel for office equipment, portable electronic devices, or televisions as described in claim 8, wherein the second hard coat layer has at least one of anti-reflective properties, anti-fouling properties, anti-static properties, and weather resistance.
10. A front panel for office equipment, portable electronic devices, or televisions described in any one of claims 6 to 9, comprising, as polycarbonate resin (a1), a component derived from a monohydric phenol represented by the following general formula (5): 【Chemistry 10】 (In the formula, R 1 represents an alkyl group having 8 to 36 carbon atoms or an alkenyl group having 8 to 36 carbon atoms, and R 2 to R 5 each independently represent a hydrogen atom, a halogen, or an alkyl group having 1 to 20 carbon atoms or an aryl group having 6 to 12 carbon atoms which may have a substituent, and the substituent is a halogen, an alkyl group having 1 to 20 carbon atoms, or an aryl group having 6 to 12 carbon atoms.)
Citation Information
Patent Citations
Anti-glare film, Anti-glare polarizing plate, and image display device
JP2009122645A
Antiglare polarizing plate and image display using the same
JP2009210592A
Anti-glare film, Anti-glare polarizing sheet, and image display device
JP2010102072A
Anti-glare film, Anti-glare polarizing sheet, and image display device
JP2010102186A
Anti-glare film, Anti-glare polarizing plate, and image display device
WO2009054287A1